2003
DOI: 10.1117/12.483896
|View full text |Cite
|
Sign up to set email alerts
|

Application of smart material-hydraulic actuators

Abstract: The application of a new class of actuators is considered. The actuators under development combine a high energy density smart material, specifically a piezoelectric material, with internal servohydraulic components. Large displacement outputs are produced, while the high force capacity of the stiff smart material is retained, for a net highenergy output. The actuator is considered "power-by-wire" because only electrical power is provided from the vehicle or system controller. A primary motivating application … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
21
0
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 7 publications
0
21
0
1
Order By: Relevance
“…are reported in Refs. [5,6]. Material selection for mechanical design of micro sensors and micro actuators are discussed in Ref.…”
Section: Introductionmentioning
confidence: 99%
“…are reported in Refs. [5,6]. Material selection for mechanical design of micro sensors and micro actuators are discussed in Ref.…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9][10] To realize these improvements, there is a need to develop new actuators to replace the function of the centralized hydraulic components; accordingly, smart material electro-hydrostatic actuators (SMEHAs) can be used to do this work. 5,7,11 Recently, substantial research has been completed on the development of electro-hydrostatic actuators (EHAs) driven by various smart materials as follows: 5,12 Konishi et al 13 in 1993 developed one of the first reported hybrid hydraulic actuators. The maximum output power of the piezoelectric stack-based actuator was 34 W at a working frequency of approximately 300 Hz and a static bias pressure of 3 MPa.…”
Section: Introductionmentioning
confidence: 99%
“…Various smart materials have been developed for potential use in aerospace, automotive, and robotic applications. [1][2][3]5,7,10,11,[26][27][28] However, piezo-stacks generate significant heat mainly due to the hysteresis losses that can deteriorate their performance and permanently damage the piezomaterial at high driving frequencies. In contrast, a giant magnetostrictive material (GMM) are more robust than piezo-stacks, especially at high temperatures, while offering approximately the same bandwidth and higher maximum induced strain compared with the piezoelectric stacks.…”
Section: Introductionmentioning
confidence: 99%
“…9 The primary advantage compared to traditional hydraulics is the power-by-wire aspect, i.e. the elimination of hydraulic distribution lines.…”
Section: Introductionmentioning
confidence: 99%
“…Electronic drive of the actuator is also a consideration, though it is discussed elsewhere. 9 Like many systems, the overall design is an integrated and iterative one, where individual components can be designed, but then require redesign to work well with other subsystems. Testing at the component, subsystem and system level aids in The remainder of the paper describes basic concepts in solid-fluid actuation, illustrating operation and highlighting limitations.…”
Section: Introductionmentioning
confidence: 99%